Movement pattern of red seabream Pagrus major and yellowtail Seriola quinqueradiata around Offshore Wind Turbine and the neighboring habitats in the waters near Goto Islands, Japan - Khyria Swaleh Karama (Aquaculture and Fisheries, 2021)
We investigated movement pattern of commercial important fish around Offshore Wind Turbine (OWT) and neighboring habitats in Goto Islands. We tagged 55 individuals of 2 fish species and released around the OWT in 2017. (27 Pagrus major from 1st Feb 2017 to 16th Mar 2017 (winter), 8 P. major and 20 Seriola quinqueradiata from 13th July 2017 to 13th Oct 2017 (summer)). Acoustic receivers were deployed at OWT, south artificial reef (AS), trapnet (TN), north FAD (F1) and south FAD (F2) in winter and two more receivers were deployed at north artificial reef (AN) and natural reef (NR) in summer. We observed 12 P. major at OWT for a day after released in winter, majority of fish (13 individuals) were detected at TN. In summer, 7 P. major were observed at OWT, 1 visited TN within the day, but others disappeared. Ten S. quinqueradiata stayed at OWT longer than P. major after released and disappeared within 2 days. They mostly moved around AS, AN, NR. Residence time from K-M curve was 10 days for P. major in winter, a day in summer and 3 days for S. quinqueradiata. Both species showed low affinity for OWT as recorded low residency index despite the season.